TEACHING READING COMPREHENSION BY USING 3-2-1 STRATEGY TO THE TENTH GRADE STUDENTS OF SMA ETHIKA PALEMBANG - Lili Marlini (Edukasi, 2015)
The objective of the study is to find out the whether or not there is a significant difference on reading comprehension achievement who are taught by using 3-2-1 strategy than those who are taught by using teacher strategy to the tenth grade students of SMA Ethika Palembang. The population of this study consisted 130  of tenth grade students of SMA Ethika Palembang in academic 2013/2014. The sample selected using convenience sampling. There were two groups, the class X1 as the experimental group and X2 as the control groups, each of groups which consisted of 30 students. The data were collected by using multiple choice reading tests. The data obtained were analyzed by using the match t-test. The t-obtained was 8.3 at significance level of 0.05 in two-tailed testing and df 58, the critical value 2.045.Since the value of t-obtained was higher than  the t-table. So, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. In other words, the students in the experimental group got better scores than the students in control group. The result showed that 3-2-1 strategy gives a significant difference on students’ reading achievement at tenth grade students of SMA Ethika Palembang. Therefore, the writer recommended that 3-2-1 strategy to be used by the teachers of English at SMA Ethika Palembang in teaching reading comprehension.